To comfort always a history of palliative medicine since the nineteenth century - Clark, David 1953- (Oxford medical histories series, 2016)
Palliative medicine was first recognised as a specialist field in 1987. One hundred years earlier, London based doctor William Munk published a treatise on 'easeful death' that mapped out the principles of practical, spiritual, and medical support at the end of life. In the intervening years a major process of development took place which led to innovative services, new approaches to the study and relief of pain and other symptoms, a growing interest in 'holistic' care, and a desire to gain more recognition for care at the end of life. This book traces the history of palliative medicine, from its nineteenth-century origins, to its modern practice around the world. It takes in the changing meaning of 'euthanasia', assesses the role of religious and philanthropic organisations in the creation of homes for the dying, and explores how twentieth-century doctors created a special focus on end of life care. 'To comfort always' traces the rise of clinical studies, academic programmes and international collaborations to promote palliative care. 0It examines the continuing need to support development with evidence, and assesses the dilemmas of unequal access to services and pain relieving drugs, as well as the periodic accusations of creeping medicalization within the field. This is the first history of its kind, and the breadth of information it encompasses makes it an essential resource for those interested in the long-term achievements of palliative medicine as well as the challenges that remain